Figurative Language Analysis of the Poetry “I Want” by Sapardi Djoko Damono - Yuni Ratna Purwaningsih (Journal on Education, 2023)
The aim of this research was to analyze the poetry by Sapardi Djoko Damono on the title “I Want” with a figurative language method. The type of this research was descriptive qualitative and took the data by note of the poetry. The data was collected and analyzed by taking several phrases of the poetry. The results of the figurative language analysis of the poem "I Want" which was written in 1989 has the theme of love and was written by Sapardi Djoko Damono. Written with the meaning of a love that is really simple, knowing the true meaning using the figurative language method, along with the discussion. Therefore it could be concluded that the meaning of the poetry is closely related to the theme of love which conveys the poet's desire to love his lover sincerely and lovingly, not about conveying sweet and great words through real actions.